THE REDESIGN STRATEGY AT REGION GENERAL HOSPITAL TYPE B IN MAGELANG CITY - Prananda Fadhlul Husna; Sri Yuliani; Ahmad Farkhan (ARSITEKTURA, 2018)
Health is the prosperous state of the body, soul and social that must always be maintained by way of periodic checks to the hospital. The hospital is health care institutions that provides patient care with medical personsl, specialized nurses and medical equipments that need to be accredited to improve public services. The purpose of this redesain strategy is to formulate the concept of planning and design of Tidar Hospital of Magelang City that meet the criteria of the future. Redesign of RSUD Tidar in Magelang was conducted based on Hospital Building Technical Guidelines in 2012. The research method is divided into three levels, programming, planning and design. Based on the results of the analysis study in field, the redesign has been obtained from the application of the Hospital Building Technical Guidelines. It should be designed on the outpatient installation can make the waiting area wider and the circulation of patients with the officers can be separated. The parking area is placed on the basement area so it is wider. For Emergency Installation is placed close to the main door so that the patient can go directly to this area and the circulation separate from the syringe to the inpatient and service area. Most of room programmes are designed based on universal accessibity.